DOES PERCEIVED GOVERNMENTAL EFFICIENCY IN MANAGING TAX MONEY DRIVE COMPLIANCE? EVIDENCE FROM A TAX GAME - BĂTRÂNCEA LARISSA-MARGARETA; NICHITA RAMONA-ANCA; BĂTRÂNCEA IOAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2012)
Tax compliance, i.e. citizens’ disposition to pay taxes either voluntary or enforced, is an extremely importanttopic at any moment, but mostly when governments have to finance public goods with few tax money. In the light ofthese realities, governments have to find ways of providing public goods by boosting tax compliance. In order toachieve this goal, various factors influencing compliance have to be considered among which the efficiency of thegovernment in managing tax money. In an experimental tax game preceded by a self-reported tax complianceattitudes questionnaire, we show that the information concerning government’s efficiency significantly influencestax payments. Moreover, tax compliance attitudes act as a mediator between the independent variable scenario (i.e.,information about government efficiency) and the dependent variable tax payments.